"THE URGENCY OF HORIZONTAL SUPERVISION (JUDICIAL SCRUTINY) OF LEGAL AID IN PRE-TRIAL AS PART OF THE HUMAN RIGHTS OF SUSPECTS" - Joshua Aditya Setyanugraha; Muktiono; Abdul Madjid (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study examines the urgency of horizontal supervision (judicial scrutiny) of legal aid in pre-trial. Legal aid is a principle contained in the due process of law. The research method used in this study is normative research with a conceptual approach and a case approach. Horizontal supervision in the current pre-trial concept does not include legal aid as an object of judge's authority so that for suspects who are not accompanied by legal counsel as required by Article 56 of the Criminal Procedure Code, the assessment must be submitted to the trial examination. Furthermore, how should horizontal supervision of legal aid provide human rights guarantees to suspects? Horizontal supervision carried out by pre-trial judges or in the future through the concept of Preliminary Examining Judges, it is appropriate to provide a balance between the great power of the apparatus administering the pre-trial function, with the human rights of suspects, including legal aid which is a universal right, so that due process of law can be achieved.